Acute Pericoronitis of Lower Third Molar: A Case Report - Sharon Sesita Frinces; Ika Andriani (Journal of Indonesian Dental Association, 2023)
Introduction: Pericoronitis is defined as an inflammation of the soft tissue around the crown of impacted tooth or partially erupted tooth. The main cause of pericoronitis is the limited space around third mandibular tooth and the overlying gingival flap. Case report: A 23-year-old patient came to RSGM UMY of operator’s motivation to treat her lower left tooth. Initially patient felt her gums were swollen and painful in the past 3-year. Objective examination showed an operculum covering distolingual and distobuccal side of 38 teeth with operculum probing depth 3,5 mm, Bleeding on Probing (-), palpation (-), Oral health Index 0.83 and Plaque index 11.3%. Treatment planning for this patient was initial therapy on the first visit. The second visit was operculectomy. The third visit was weekly control. Results: Two weeks after operculectomy procedure showed a post operculectomy area with a wound that had entered the healing phase (remodelling) with operculum probing depth 3,5 mm, Bleeding on Probing (-), palpation (-), Oral health Index 0.83 and Plaque index 10.3%. Conclusion: Surgical approach such as operculectomy is done and known as the golden standard to treat pericoronitis. Operculectomy is known as the most favourable treatment as it is simple, easy to perform, less time consuming, and believed as the most effective method for treating pericoronitis. The goal of operculectomy is to enforce a minimal or no post-operative complications and proper wound healing.